The Association Between Acquired Color Deficiency and PET Imaging of Neurodegeneration in Mild Cognitive Impairment and Alzheimer Disease - Vidal, Kallene Summer Moreira; Decleva, Diego; Barboni, Mirella Telles Salgueiro; Nagy, Balazs Vince; De Menezes, Paulo Augusto Hidalgo; Aher, Avinash; Coutinho, Artur Martins; Squarzoni, Paula; Faria, Daniele De Paula; Duran, Fabio Luis De Souza; Buchpiguel, Carlos Alberto; Kremers, Jan; et al. (Investigative Ophthalmology & Visual Science, 2022)
PURPOSE. To evaluate color vision changes and retinal processing of chromatic and lumi-nance pathways in subjects with Alzheimer disease (AD) and mild cognitive impairment (MCI) compared with a matched control group and whether such changes are associated with impaired brain glucose metabolism and beta-amyloid deposition in the brain.METHODS. We evaluated 13 patients with AD (72.4 +/- 7.7 years), 23 patients with MCI (72.5 +/- 5.5 years), and 18 controls of comparable age (P = 0.44) using Cambridge color test and the heterochromatic flicker ERG (HF-ERG). The Cambridge color test was performed using the trivector protocol to estimate the protan, deutan and tritan color confusion axes. HF-ERG responses were measured at a frequency of 12 Hz, which ERGs reflect chromatic activity, and at 36 Hz, reflecting luminance pathway. A study subsample was performed using neuropsychological assessments and positron emission tomography.RESULTS. Patients with AD presented higher mean values indicating poorer color discrim-ination for protan (P = 0.04) and deutan (P = 0.001) axes compared with the controls. Along the tritan axis, both patients with AD and patients with MCI showed decreased color vision (P = 0.001 and P = 0.001) compared with controls. The analyses from the HF-ERG protocol revealed no differences between the groups (P = 0.31 and P = 0.41). Diffuse color vision loss was found in individuals with signs of neurodegeneration (protan P = 0.002, deutan P = 0.003 and tritan P = 0.01), but not in individuals with signs of beta-amyloid deposition only (protan P = 0.39, deutan P = 0.48, tritan P = 0.63), regardless of their clinical classification.CONCLUSIONS. Here, patients with AD and patients with MCI present acquired color vision deficiency that may be linked with impaired brain metabolism.
CRIS-Team WoS Importer:2023-04-28